IMPACT ASSESSMENT OF LINER SCHEDULE DISRUPTION ON FLEET EFFICIENCY BASED ON TIME CHARTER EQUIVALENT - Drozhzhyn, O. L.; Onyschenko, S. P. (Systems and Technologies, 2025)
The article discusses the problem of liner schedule disruption (LSD) and its impact on the economic efficiency of shipping companies. It has been determined that failure to comply with container ship schedules leads to direct economic losses, which are reflected in a decrease in the time charter equivalent (TCE) indicator, which is a universal indicator of the profitability of ship operation regardless of the form of chartering. It is shown that schedule disruptions have a double negative effect: on the one hand, a decrease in efficiency due to an increase in voyage time, and on the other hand, a deterioration in the carrier’s image, which in the long term reduces demand and market share. The paper proposes a mathematical model for quantitative assessment of losses from delays in port and during the voyage. Analytical dependencies allow determining the decrease in TCE due to an increase in downtime in ports and the time a vessel spends in sea transit. The calculations showed that delays during ship movement are 2–3 times more costly than delays of equivalent duration in port, due to high bunker fuel costs and the need to recover the schedule by increasing speed. The assessment methodology developed by the author allows analyzing the economic consequences of schedule non- compliance for both individual voyages and the entire line or fleet of the company as a whole. It takes into account the difference in the size of vessels and their contribution to the total volume of transportation, which ensures the adequacy of the assessment in strategic planning. The results obtained are of practical importance for optimizing management decisions in the field of liner shipping, in particular for improving the reliability of schedules, minimizing operational risks, and reducing financial losses. Thus, the proposed approach transforms the abstract problem of schedule disruption into a specific financial indicator that can be used as a tool for monitoring performance and making decisions in real time, as well as for long-term strategic planning of container transport development.